2021
DOI: 10.1111/and.14114
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of aqueous extract of fermented rooibos (Aspalathus linearis) on human sperm function

Abstract: Aspalathus linearis (rooibos) is a herbal medicinal plant originally from South Africa's fynbos and well known for its medicinal effects in treating different medical conditions. Rooibos contains significant levels of antioxidants capable of inhibiting the production of reactive oxygen species, which may improve seminal parameters. This study focussed on investigating the direct effect of fermented rooibos on human sperm functions in vitro. Semen samples collected by masturbation from unproven fertile donors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The washed samples were incubated with black tea aqueous extract (0.4, 4.0, 40, and 405 μg/ml) for 1 hr at 37°C. Additional sperm parameters, sperm motility, vitality, mitochondrial membrane potential (MMP), ROS production, DNA fragmentation, capacitation, and acrosome reaction, were analyzed as previously described [32,[35][36][37][38]. The control contained only HTF-BSA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The washed samples were incubated with black tea aqueous extract (0.4, 4.0, 40, and 405 μg/ml) for 1 hr at 37°C. Additional sperm parameters, sperm motility, vitality, mitochondrial membrane potential (MMP), ROS production, DNA fragmentation, capacitation, and acrosome reaction, were analyzed as previously described [32,[35][36][37][38]. The control contained only HTF-BSA.…”
Section: Methodsmentioning
confidence: 99%
“…The SCA was used to assess the motility of treated sperm suspension (2 μl) on Leja slides and incubated at 37°C. Moreover, analysis was done on the following: beat cross frequency (BCF), linearity (LIN), straightness (STR), amplitude of lateral head displacement (ALH), wobble (WOB), average velocity path (VAP), velocity curve line (VCL), velocity straight line (VSL), and total motility [32,37].…”
Section: Sperm Motility and Kinematicmentioning
confidence: 99%
“…Another study also reported on the reduction of sperm DNA aberration after treatment with a variety of vitamins E and C (400 mg each), β-carotene (18 mg), zinc selenium, or a mixture of 30 mg β-carotene, 180 mg of vitamin E and fatty acids ( Punjabi et al 2022 ). Furthermore, several studies have revealed antioxidant therapy to improve sperm quantity and quality ( Büyükleblebici et al 2014 , Moichela et al 2021 , Takalani et al 2021 , Setumo et al 2022 ).…”
Section: Management Of Mosimentioning
confidence: 99%
“…The samples were mixed with HTF-BSA (1:6) (Moichela et al 2021;Takalani et al 2021), washed by centrifugation (300×g; 10 min) and re-suspended. Sperm suspensions (15 × 10 6 /mL) were subsequently incubated for 1 h with green tea aqueous extracts (0 μg/mL, 0.4 μg/mL, 4.0 μg/mL, 40 μg/mL and 405 μg/mL) at 37 o C. Human tubular fluid supplemented with BSA served as the control.…”
Section: Collection and Preparation Of Human Semenmentioning
confidence: 99%